Post-Soviet Scandinavian Country – Estonia and Its Politics of Remembrance after 1991 - Ciesielska, Joanna (Sensus Historiae, 2023)
The aim of the work is to analyze Estonian memory policy after 1991 and to attempt to consider its cultural affiliation to the Nordic circle, as well as to indicate the activities undertaken by the Office of the Nordic Council of Ministers in Estonia, thanks to which the Nordic and Baltic regions would be brought closer together. After a short introduction, we get to know the lectures of Sofi Oksanen - an important intellectual of Finnish-Estonian origin. Then, the “orientation towards the North” in Estonian relations with Europe was described and the signs of the identification of Estonians with Nordic culture in cultural life and international politics were analyzed. The issue of creating a new historical narrative in Estonia after 1991 was also discussed. The next part describes the activities of the Office of the Nordic Council of Ministers in Estonia. The work ends with a summary of the conclusions from the text and a map showing the quality of life in individual European countries (as of 2022).